Crystal structure refinement a crystallographers guide to SHELXL - d (Oxford : Oxford University Press, 2006)
A crystallographers guide to SHELXL, covering various aspects of practical crystal structure refinement, from the treatment of hydrogen atoms to the assignment of atom types, and more. After an introduction to SHELXL, a brief survey of crystal structure refinement is provided.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Crystals -- Structure; Crystals -- Refining; Crystals -- Data processing